Effectiveness of Digital journalism in developing political awareness among Iraqi feminist activists "A survey study" - Ghintab, Azhar Sabeeh (ALBAHITH ALALAMI, 2022)
The paper aims to reveal the effectiveness of digital journalism in developing political awareness among Iraqi feminist activists. This paper is descriptive, and it adopted the analytical descriptive survey method. A snowball sample composed of (102) respondents of Iraqi feminist activists was adopted and questionnaire was used to collect data. The research has reached the following conclusions: The rate of Iraqi Feminist Activists dependence on digital Journalism have increased; to develop their political awareness, and their preference - in this regard - (the pages of journalistic institutions to social media) in a way that exceeds other types of digital journalism. (Variety of languages) has topped the priorities of Iraqi feminist activists regarding the richness of digital journalism they depend on; to develop their political awareness. No statistically significant differences were found among Iraqi feminist activists based on their demographic variables and their priorities regarding the richness of digital journalism they depend on; to develop their political awareness. A positive and strong significantly statistical relationship was found between the effectiveness of digital journalism represented by its cognitive, emotional, and behavioral effects related to the political awareness of Iraqi feminist activists, and their priorities regarding the richness of that journalism.